Nanophotonic-structured front contact for high-performance perovskite solar cells - Akhtaruzzaman M.; Hossain M.I.; Islam M.A.; Shahiduzzaman M.; Muhammad G.; Mahmud Hasan A.K.; Tsang Y.H.; Sopian K. (Science Press (China), 2023)
Absorption spectroscopy; Chromium compounds; Conversion efficiency; Electron transport properties; Light; Light absorption; Magnetron sputtering; Metals; Nanophotonics; Open circuit voltage; Perovskite; Perovskite solar cells; Zinc oxide; Device stability; Electrical effects; Magnetron-sputtering; Optic and electrical effect; Optoelectronics devices; Optoelectronics property; Performance; Ultra-violet light; Ultraviolet stability; ZnO:cr front contact; II-VI semiconductors